Effect of partial lockdown due to Covid-19 pandemic on PM10 concentration in Belo Horizonte, Brazil - Ricardo Gomes Passos; Stela Dalva Santos Cota; Maria Ângela de Barros Correia Menezes; Helena Eugênia Leonhardt Palmieri; Lúcia Maria Laboissière de Alencar Auler (Desenvolvimento e Meio Ambiente, 2021)
Despite their proven effectiveness in combating the pandemic of COVID-19, measures of social isolation, quarantines, and lockdowns have drastic consequences in the social and economic spheres. This paper presents results from an ongoing study in Belo Horizonte, Brazil, to evaluate the effect of social isolation on MP10 concentration. The monitoring point was chosen in a wooded area within a university campus. Social isolation was analyzed in terms of vehicle movements recorded by speed cameras, during all phases following the partial lockdown (PL) instituted in the city. The social isolation index (SDI) showed a maximum isolation percentage of 49.5%, reached in the first week of the PL, with a subsequent continuous downward trend. The results showed a 65.2% reduction in PM10 due to the PL, when comparing the mean values monitored before (22.2 ± 3.0 µg m-3) and during (7.7 ± 4.2 µg m-3) the PL. The relationship between vehicle movement and PM10 concentrations in the monitoring region was evidenced and found to be significant (r(XY) = 0.782, p-value = 0.000). Such reduction, observed in such a short term, but due to force majeure, certainly has beneficial effects on the population's health, reinforcing the reflection about the positive impacts that could come with policies that favor the reduction of vehicle movement in the cities.